VARIATION IN MINERALS CONTENT IN FRUITS OF PEPPER (CAPSICUM ANNUUM L.) LANDRACES, GROWN IN GREENHOUSE - Chávez-Servia, José Luis; Vera-Guzmán, Araceli; Carrillo-Rodríguez, José C.; Heredia-García, Elena (Vitae, 2016)
Background: Malnutrition is a major health problem in developed and developing countries, and in Latino American, a viable option is reconsider the pre-Columbian and traditional diets based on endemic species. In Mesoamerica, the chilli or pepper (Capsicum annuum L.) played an important role, and its contribution remain until today in the Mexican gastronomy. Objective: the aim of the present work was to evaluate the variation among and within five morphotypes of pepper (C. annuum L.) native of Oaxaca, Mexico, in relation to minerals content in fruits. Methods: a collection of 45 population samples of chilli pepper, which were grouped in five morphotypes named as chile de Agua, Tabiche, Piquin, Solterito and Nanche, and later planted in greenhouse conditions under a complete blocks randomized design with three replications. At harvest time a fruit samples from 300 to 500 g per population were obtained, and later the samples were incinerated to obtain ashes, which were solubilized in acid medium. The determinations of Cu, Fe, Mg, Zn, Na, K, and Ca were done by atomic absorption spectrometry, and the S and P elements were quantified by an UV-vis spectrometer. Results: in the analysis of variance, significant differences (P < 0.05) were determined among and within morphotypes of C. annuum over all macro and trace elements. Solterito presented the highest values in eight mineral elements, after Piquin and chile de Agua were the second more important. In Fe content, Piquin and Solterito showed high values between 8.0 and 8.5 mg/100 g of dry sample weight. Into each morphotype, the outstanding populations were: CAG03 and CAG10 from chile de Agua; CNA02 of Nanche; CPI02 and CPI09 of Piquin type; CSO01, CSO02 and CSO03 from Solterito; and CTA02 and CTA05 from Tabiche type. The differences among morphotypes were confirmed in the multiple discriminant analysis and the Mahalanobis’ distances. Conclusions: The results showed differences among and within morfotypes of C. annuum, and the minerals content reported indicate that, the chilli pepper is a food with high nutritional values. In fact 100 g of dry weight, potentially can supply the dairy needs of Cu, Mg, P and an important proportion of the needs of Fe, Zn and K, among other nutritional elements.